The Impact of Online Gambling Activities on Families: A Case Study in Pilang Village - Muhammad Ilham Mauludi; Mardiana Mardiana (Interpersonal: Jurnal Bimbingan Konseling Islam, 2026)
The aim of this study is to assess and examine the impact of online gambling on the socio-economic status of residents in the Pilang sub-district of Probolinggo city. Internet-based gambling, which utilizes the internet and various game options accessible via electronic devices such as cellphones with comprehensive and user-friendly applications, poses significant issues due to its negative socio-economic repercussions and its infringement on socio-economic factors and cultural-religious norms. This results in legal consequences under both Islamic law and governmental regulations laws, prompting numerous countries, including all Islamic nations, to ban this type of gambling. The The research is a qualitative study with a descriptive approach. study that employs interviews with multiple sources and observations in the study area. Findings reveal that online gambling adversely affects social values, religious principles, and contributes to social problems. Economically, it undermines family financial stability, particularly impacting the families of those who gamble online.